2014
DOI: 10.1159/000365055
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant <b><i>Staphylococcus aureus </i></b>Infection: An Independent Risk Factor for Mortality in Patients with Poststernotomy Mediastinitis

Abstract: Objective: The mortality rate of patients with poststernotomy mediastinitis remains very high. The aim of this study was to identify the risk factors associated with mortality in these patients. Subjects and Methods: Surveillance of sternal surgical-site infections including mediastinitis was carried out for adult patients undergoing a sternotomy between 2004 and 2012. Criteria from the US Centers for Disease Control and Prevention were used to make the diagnosis. All data on patients with a diagnosis of media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…Even if the mortality is very high, the only adequate antibiotic therapy seems insufficient, as survival data showed. This study also supports the finding that delayed appropriate antibiotic therapy will result in a statistically significant increase in mortality [ 1 ].…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Even if the mortality is very high, the only adequate antibiotic therapy seems insufficient, as survival data showed. This study also supports the finding that delayed appropriate antibiotic therapy will result in a statistically significant increase in mortality [ 1 ].…”
supporting
confidence: 89%
“…Yavuz et al [ 1 ] investigated independent risk factors in patients suffering from PSM. The study clearly showed that improvement of infection control interventions can dramatically decrease SSI rates.…”
mentioning
confidence: 99%